Cecal Bascule in a COVID-19 Positive Patient: Case Report - Curmi, Arthur; Cuschieri, Robert (The Surgery Journal, 2022)
Cecal volvulus is an uncommon cause of acute intestinal obstruction accounting for around 10% of intestinal volvuli. There are three main variants of cecal volvuli including the axial, loop, and bascule types. Diagnosis is confirmed via a computed tomography scan and surgery is the mainstay treatment due to a high risk of morbidity and mortality. Here we report a rare presentation of cecal volvulus in a COVID-19 positive patient that was complicated by an anastomotic leak.
Keywords: volvulus; bascule; cecum; obstruction; anastomotic leak; case report